Relationship between body weight and blood biochemical measurements resulted from sniffing lead-containing substances of homeless adolescent in Khartoum City, Sudan - Hamed, Leila M. A.; Nogod, Gaafar K.; Saeed, Hythem S.A.; Abdellah, Abdelmonem M. (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
Sniffing lead-containing substances phenomenon is associated with possible brain damage and severe breathing problems. In this study, a total of 120 sniffers and 40 normal children as control were randomly selected to investigate the effect of sniffing lead-containing substances on the biochemical parameters: Lead (mg/dl), calcium (mg/dl), total protein (mg/dl), albumin (mg/dl), total bilirubin (mg/dl), direct bilirubin (mg/dl), indirect bilirubin (mg/dl), AST (U/L), ALT (U/L), cholesterol and triglyceride. Result indicated that all of the studied biochemical parameters were not significantly affected by age of sniffers, but some parameters such as lead, total bilirubin and indirect bilirubin were slightly increased with the increase of sniffers age. Accordingly, long-term of sniffing lead-containing substances causes negative influence on children’s intelligence and behavioral development.